Rosemary (Salvia rosmarinus): Health-Promoting Benefits and Food Preservative Properties - Jacob, P. Veenstra; Jeremy, J. Johnson (International Journal of Nutrition, 2021)
Natural food preservatives in the form of herb extracts and spices are increasing in popularity due to their potential to replace synthetic compounds traditionally used as food preservatives. Rosemary (Salvia rosmarinus) is an herb that has been traditionally used as an anti-inflammatory and analgesic agent, and currently is being studied for anti-cancer and hepatoprotective properties. Rosemary also has been reported to be an effective food preservative due to its high anti-oxidant and anti-microbial activities. These properties allow rosemary prevent microbial growth while decreasing food spoilage through oxidation. Rosemary contains several classes of compounds, including diterpenes, polyphenols, and flavonoids, which can differ between extracts depending on the extraction method. In particular, the diterpenes carnosol and carnosic acid are two of the most abundant phytochemicals found in rosemary, and these compounds contribute up to 90% of the anti-oxidant potential of the herb. Additionally, several in vivo studies have shown that rosemary administration has a positive impact on gastrointestinal (GI) health through decreased oxidative stress and inflammation in the GI tract. The objective of this review is to highlight the food preservative potential of rosemary and detail several studies that investigate rosemary to improve in vivo GI health.
Keywords: Food preservative; Rosemary; phytochemical; anti-oxidant; anti-microbial; gastrointestinal health